SODIUM ACCUMULATION IS ASSOCIATED WITH DISABILITY AND PROGRESSION IN MULTIPLE SCLEROSIS: A 23NA MRI STUDY. Issue 11 (9th October 2013) - Paling, David; Solanky, Bhavana; Riemer, Frank; Tozer, Daniel; Wheeler–Kingshott, Claudia; Kapoor, Raju; Golay, Xavier; Miller, David
Abstract : Introduction: Neuroaxonal loss is the major pathological substrate of irreversible disability in Multiple Sclerosis (MS). Sodium is maintained at lower concentration within the intra–axonal space by the Na/K/ATPase pump. In MS, failure of the pump secondary to neuroaxonal metabolic dysfunction increases the intracellular sodium concentration, which in turn leads to neuroaxonal loss by causing intra–axonal calcium import. 1 Since sodium is at higher concentration within the extracellular space, neuroaxonal loss and replacement with extracellular fluid also increases sodium concentration. Sodium (23Na) magnetic resonance imaging enables quantitation of total sodium concentration in the brain, and could help to quantify the extent neuroaxonal dysfunction and loss in different tissue types and different MS subgroups in vivo, and their association with clinical disability. Previous studies have shown increased sodium concentration in lesions, normal appearing white matter (NAWM) and grey matter in patients with relapsing remitting MS (RRMS) 2 3 however whether similar increases are seen in patients with primary progressive MS (PPMS) and secondary progressive MS (SPMS) and whether sodium accumulation is associated with disability in these patients is not known. Methods: We performed 23Na MRI imaging on 27 healthy controls, 27 patients with RRMS, 23 patients SPMS and 20 patients with PPMS. Sodium concentration was quantified in segmented NAWM, cortical grey matter, basal ganglia and T2 hyperintense, T1 hypointense and T1 isointense lesions. Results: Cortical sodium concentrations were significantly higher in all subgroups of MS compared to controls, and NAWM and basal ganglia sodium concentrations were higher in PPMS and SPMS compared to controls. T2 hyperintense, T1 hypointense and T1 isointense lesion sodium concentrations were higher than NAWM. Sodium concentrations were higher in SPMS compared to RRMS in cortical grey matter (mean 41.3±4.2mM vs. 38.5±2.8 mM, p=0.028), NAWM (36.1±3.5 mM vs. 33.6±2.5 mM, p<0.001), and basal ganglia (38.1±3.1 mM vs. 35.7±2.4 mM, p=0.02). Sodium concentrations were also higher in T1 hypointense lesions in PPMS (49.3±8.0 mM vs. 43.0 mM, p=0.029) and SPMS (49.0±7.0 mM vs. 43.0±8.5 mM) compared to RRMS. Multivariate analysis showed significant independent associations of basal ganglia sodium concentration with EDSS (coefficient=0.244, p=0.003) and timed 25ft walk speed (coefficient=–0.24, p=0.01), and of T1 lesion sodium concentration with the z scores of the 9 hole peg test (coefficient –0.12, p<0.001) and paced auditory serial addition test (coefficient =–0.08, p<0.001). Conclusions: Significant increases in sodium were seen in lesions and normal appearing brain tissues in MS. Increased concentration of sodium in lesions, cortical grey matter, NAWM and basal ganglia in SPMS versus RRMS indicates greater neuroaxonal metabolic dysfunction and/or loss in the former group. MRI measurement of sodium concentration in vivo is likely to reflect clinically relevant neuroaxonal pathophysiology and may be a useful outcome measure in trials of putative neuroprotective treatments.